Clinical and parasitological response to oral chloroquine and primaquine in uncomplicated human Plasmodium knowlesi infections - Daneshvar, C.; Davis, T.M.E; Cox-Singh, J.; Mohammad Zakri, Rafa’ee; Siti Khatijah, Binti Zakaria; Paul C, Divis; Balbir, Singh (BioMed Central Ltd., 2010)
Background: Plasmodium knowlesi is a cause of symptomatic and potentially fatal infections in humans. There are no studies assessing the detailed parasitological response to treatment of knowlesi malaria infections in man and whether antimalarial resistance occurs.